Path Analysis of the Influence of the Theory of Planned Behavior Construct on Visual Inspection of Acetic Acid Uptake in Banjarnegara - Amalia Khurotul Mahzunah; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: The death rate for women of childbearing age is increasing. This indicates the need for useful interventions to prevent deaths from cervical cancer. One way is to carry out an Acetic Acid Visual Inspection (VIA) screening. Unfortunately, the rate of VIA screening is still low. So it is necessary to conduct research on how the behavior of using VIA screening is viewed from health promotion theory. This study aimed to determine the application of one of the health promotion theories, namely the Theory of Planned Behavior (TPB), to the use of VIA screening in Banjarnegara Regency. Subjects and Method: The study was conducted with a cross-sectional study design involving 200 female participants of reproductive age ranging from 20 to 50 years. This research was conducted in Banjarnegara Regency, Central Java Province, Indonesia. This study was conducted in April-May 2024. The sample was selected using fixed disease sampling to find participants who had undergone VIA screening. Data collection was carried out using questionnaires and data was analyzed using univariate, bivariate and path analysis. Results: The results of this study showed that the behavior of using VIA screening was directly influenced by intentions and perceived behavioral control. The possibility of subjects to undergo VIA screening can increase by strong intentions (OR= 6.56; 95% CI= 2.97 to 14.48; p< 0.001) and high perceived behavioral control (OR= 6.23; 95% CI= 3.07 to 12.65; p < 0.001). In addition, the results of path analysis showed that intentions were influenced by attitudes (OR= 2.73; 95% CI= 1.31 to 5.69; p= 0.007), subjective norms (OR= 3.48; 95% CI= 1.71 to 7.07; p= 0.001), and perceived control treatment (OR= 3.03; 95% CI= 1.50 to 6.09; p= 0.002). Conclusion: The use of VIA screening is directly influenced by intention and perceived behavioral control. In addition, intentions are influenced by attitudes, subjective norms, and perceived behavioral control. All results of the analysis are statistically significant.